TRANSLATION OF UKRAINIAN CIVIL LAW TERMS FROM UKRAINIAN INTO ENGLISH – CASE STUDY - Kizinska, Anna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
Aim: In the research paper there have been analysed Ukrainian civil law terms and their English equivalents. There have been determined the translation methods applied while forming the equivalents in question. The reserach results have preliminarily confirmed the hypothesis according to which the translation methods determined in the research do appear among the translation methods in the classification of methods applied while translating Polish civil law terms into English. Methods: The terms under analysis constitute incongruent terms (according to the definition by Šarčević), as well as legal terms (according to the definition by Morawski). The appearance of the equivalents has been checked in the British law database, legislation.gov.uk and the general English database, sketchengine.eu. The definitions of the equivalents have been checked in four British law dictionaries. The classification of the translation methods applied while translating Polish incongruent civil law terms into English was published in 2018. Results: The results of the analysis have preliminarily confirmed the hypothesis according to which the translation methods determined in the research do appear among the translation methods in the classification of methods applied while translating incongruent Polish civil law terms into English. Originality: The results of the study constitute the first stage of establishing the classification of the translation methods applied while translating incongruent Ukrainian civil law terms into English. Practical significance: The discussion on the English equivalents suggested for the Ukrainian source terms may be useful for translators dealing with Ukraininan law texts translation from Ukrainian into English.